Hiding in plain sight: children with visual perceptual difficulties in schools - McDowell, Nicola; St Clair Tracy, Helen; Blaikie, Andrew; Ravenscroft, John; Dutton, Gordon N. (Frontiers in Human Neuroscience, 2024)
Cerebral visual impairment (CVI) is increasingly being recognized as a significant cause of visual difficulties in children, particularly those with typical visual acuity, who nonetheless struggle in educational settings. This narrative review aims to elucidate the nature and impact of visual perceptual difficulties (VPD) associated with CVI in school-aged children, who often remain undiagnosed due to the current erroneous focus on visual acuity as a required diagnostic criterion for CVI. The review synthesizes findings from recent studies, highlighting that up to 3.4% of children in mainstream schools and a higher percentage in special educational settings may experience VPD, which significantly impacts upon their learning and development. The manifestations of VPDs, such as difficulties in motion perception, recognition, and visuospatial processing, are often subtle and can thus be overlooked, leading to misconceptions about the origins of the affected child’s abilities and behaviors. The review also discusses the challenges in current diagnostic processes, emphasizing the need for comprehensive history taking and assessments that go beyond standard visual acuity tests. It proposes a multi-faceted approach to identification and support, incorporating both clinical assessments and teacher/parental observations, to better address the needs of affected children. Furthermore, this paper advocates for the inclusion of VPDs in the International Classification of Diseases (ICD 11) to ensure children with these visual issues receive appropriate educational support. By integrating lived experiences of individuals with CVI and the latest research findings, this review underscores the urgent need for awareness and tailored educational strategies designed to support children with VPDs. The findings suggest that without such recognition and intervention, many children with VPDs will continue to “hide in plain sight,” facing unnecessary challenges in their educational and social development. The review concludes with recommendations for policy changes and future research directions to improve the identification, classification, and support of children with VPDs within the educational system.